2018
DOI: 10.1007/s10549-018-4712-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of intraoperative radiotherapy and external beam-accelerated partial breast irradiation in elderly breast cancer patients

Abstract: Background and purposeWe investigated the acute toxicity of accelerated partial breast irradiation using external beam (EB-APBI) or intraoperative radiotherapy (IORT) techniques in elderly breast cancer patients.Materials and methodsWomen ≥ 60 years with unifocal breast tumors of ≤ 30 mm were eligible for this prospective multi-center cohort study. IORT was applied with electrons following lumpectomy (23.3 Gy). EB-APBI was delivered using 3D-CRT or IMRT in 10 daily fractions of 3.85 Gy within 6 weeks after sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
0
20
1
Order By: Relevance
“…Nine studies reported results about accelerated partial breast irradiation (APBI): 2 focused on EB APBI ( 23 , 25 ), 2 on intraoperative RT (IORT) ( 13 , 26 ), and 2 on brachytherapy (BRT) ( 8 , 21 ). Jacobs et al compared IORT and EB-APBI ( 18 ), Smith et al compared BRT and EB-RT ( 11 ), and Meattini et al compared WBI and EB-APBI ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies reported results about accelerated partial breast irradiation (APBI): 2 focused on EB APBI ( 23 , 25 ), 2 on intraoperative RT (IORT) ( 13 , 26 ), and 2 on brachytherapy (BRT) ( 8 , 21 ). Jacobs et al compared IORT and EB-APBI ( 18 ), Smith et al compared BRT and EB-RT ( 11 ), and Meattini et al compared WBI and EB-APBI ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported data on only acute toxicity ( 13 , 18 , 21 , 24 ) while in 4 studies ( 9 , 11 , 13 , 21 ) RT technique details and/or doses were not described. Toxicity assessment was considered as the primary endpoint only in 5 studies ( 6 , 13 , 23 - 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…A study by Piotrowski et al suggested that a single IORT could be used as an alternative for 6-7 weeks of PORT [21]. Jacobs et al [22] conducted a study on the toxic reactions of IORT and concluded that, just like EBRT, IORT had toxic reactions tolerable by the patients. Moreover, a recent clinical trial entitled TARGIT-R showed that this therapy had a low wound complications incidence and local recurrence rate [23].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the incidence of seroma was 6.0% and the infection rate was 5.0%; the infection rate was thus slightly higher than that in the TARGIT-A study (Table 4), but was comparable to the matched patients undergoing BCS over the same period. The wound infection rate arising from IORT varies significantly in the currently available studies, ranging from 2.3% to 13.6% (27)(28)(29). This difference might be attributable to the different radiotherapy equipment and methods used in the studies, and to the effect that variable patient characteristics, surgical procedures, and postoperative therapies might have had on toxicity and side effects.…”
Section: Discussionmentioning
confidence: 99%